Designing Reward And Punishment Systems To Spur Awareness Of The Use Of Personal Protective Equipment On Pt. Xyz Workers - Haniffan Zikri Anugrah De Tasya; Heriyono Lalu; Sheila Amalisa Salma (eProceedings of Engineering, 2022)
Personal Protective Equipment is a tool that can protect a person whose function is to isolate part or all of the body from potential hazards in the workplace. Personal Protective Equipment is used in work in various fields, one of which is in building construction. At PT.XYZ, some workers are not disciplined in applying the regulations on Occupational Health and Safety, especially in Personal Protective Equipment. The cause of use Personal Protective Equipment is often due to forgetting to use, being uncomfortable in using, and damaged. The root of the problem that occurred in the West Sumatra flat construction project workers was the lack of occupational health and safety awareness, especially on Personal Protective Equipment use. Thus, this study aims to design a system of reward and punishment using Abraham Maslow's theoretical approach, which explains the level of human needs as motivation at work. Furthermore, the data processing method used in this research is the analytical hierarchy process. From the results of data processing obtained two factors that encourage work motivation to increase awareness of the use of Personal Protective Equipment, namely salary and health insurance. So, the reward for workers based on workers need are bonuses salary and health insurance. This research resulted in two designs, namely an awareness assessment of the use of Personal Protective Equipment and a reward and punishment system based on the needs of workers. Keywords : Reward and Punishment System, Awareness, Personal Protective Equipment, Analytical Hierarchy Process, Abraham Maslow's Theory